Development of an ESP32-Based Resistivity Meter Instrument with Integration of ACS712 Current Sensor, ADS1115 Voltage Sensor and Neo6MV2 GPS Module - Aryadi Nurfalaq; Rahma Hi. Manrulub; Irwan Ramli (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2025)
This study aims to develop an ESP32-based resistivity meter instrument integrated with an ACS712 current sensor, an ADS1115 voltage sensor, and a Neo6MV2 GPS model. This IoT-based instrument can be operated remotely so that it can streamline measurements. The method used in this study is the R&D method where this method aims to create innovations in the form of new and applicable products, systems, or models, and test their effectiveness. The research stages start from hardware design assembled based on block diagrams, software design using the Arduino IDE using the C++ programming language, testing and data collection. The results of the study showed that the ADS 1115 sensor has an average measurement error (% error) of 5.1%, the ACS 712 current sensor has an average% error of 3.6%, and the Neo6MV2 GPS module has an average latitude difference of 0.000016 degrees (1.81 m) and longitude of 0.000025 degrees (2.83 m). Measurements can be performed remotely via smartphone using the ESP32 at a distance of 41 m. Comparison of the measurement data from the IoT resistivity meter with a standard resistivity instrument were obtained in the range of 7.771% - 12.815% with an average error of 9.625%. Based on these measurement results, the resistivity values ​​ this indicates that this instrument can be used to identify mined minerals and groundwater aquifers.